ANALYSIS OF TEACHER NEEDS IN TPACK-BASED DEEP LEARNING TO IMPROVE ELEMENTARY SCHOOL TEACHERS' DIGITAL LITERACY SKILLS - Handini, Oktiana; Suryanti, Hera Heru Sri; Sutoyo (Antis-Publisher, 2026)
Objective: The rapid development of digital technology has created new demands for elementary school teachers to possess strong digital literacy skills and to integrate technology meaningfully into the learning process. This study aims to analyze elementary school teachers' needs in implementing TPACK-based deep learning to improve their digital literacy skills. Method: A qualitative descriptive approach was employed in this research. The participants consisted of 50 elementary school teachers selected through purposive sampling. Data were collected using classroom observations, semi-structured interviews, and documentation. The collected data were analyzed through data reduction, data display, and conclusion drawing, with thematic analysis based on TPACK components and deep learning characteristics. Results: The results indicate that most teachers have adequate basic technological skills, particularly in operating common digital devices and applications. However, the integration of technology with pedagogy and content knowledge remains limited. The implementation of deep learning is still low, as learning activities tend to focus on surface understanding rather than conceptual depth, reflection, and problem-solving. Teachers experience difficulties in selecting appropriate digital tools, designing technology-supported learning activities, and applying TPACK holistically. In addition, limited professional development, lack of continuous mentoring, and insufficient institutional support were identified as major challenges. This study highlights that the primary need of elementary school teachers lies in strengthening TPACK integration through practical, contextual, and sustainable professional development programs. Novelty: The novelty of this research lies in providing a comprehensive needs analysis that links TPACK, deep learning, and digital literacy within the context of elementary education, serving as a foundation for designing targeted teacher development programs.